Расчет мощности лазера и параметров оптических схем ЛДИС - Никитин, А. М. (НТУ "ХПИ", 2004)
Estimated calculation of the radiation power is adduced, permitting to receive a steady signal of a laser Doppler anemometer (LDA), for the optical systems adapted to measurements of flows characteristics in the composite channel power and heat engineering of the equipment. Efficiency of algorithm at a phase of layout LDA optical schemes is shown
Keywords: лазерные доплеровские измерители скорости; теплоэнергетическое оборудование; сигнал; оптическая среда; рассеянное излучение; лазеры